Clinical Risk Score for Invasive Pulmonary Aspergillosis in Patients With Liver Failure: A Retrospective Study in Zhejiang - Zhang, Xuan; Shen, Sijia; Dai, Xiahong; Bi, Yunjiao; Zhang, Junjie; Wu, Yuhao; Shi, Yishang; Wei, Runan; Gao, Hainv (Frontiers in Medicine, 2021)
Purpose: The mortality of invasive pulmonary aspergillosis (IPA) in patients with liver failure was high. However, the prophylactic treatment in those patients with a high-risk factor in IPA has not been researched. Patients and methods: A multicenter, retrospective study was conducted in patients with liver failure. The study cohort of liver failure was randomly split into a training set for model development and the other served as the testing set for model verification. Multivariate analysis was performed to identify the risk factors of IPA. A weighted risk score for IPA was established. Anti-fungal treatment was prophylactically used in patients with medium and high IPA risk to evaluate the effect. Results: In total, 1,722 patients with liver failure were enrolled. Fifty-seven patients who received prophylactic treatment were excluded from the risk factor system study. About 1,665 patients were randomly split at a ratio of 2:1 into two datasets. Diabetes, glucocorticoids, plasma exchange, and hepatorenal syndrome (HRS) were risk factors in IPA in patients with liver failure, with weighted risk scores of 4, 7, 2, and 3, respectively. In the validation set and test set, the patients with risk scores of ≤ 3 presented low incidences of IPA at 4 and 2.7%. Patients with risk scores of 4–5 had an IPA incidence of 7.6% and 10.1%, and could be considered as a medium-risk group (p < 0.01 vs. the group with scores of ≤ 3), whereas those with risk scores of >5 manifested a significantly higher IPA incidence of 21.2 and 12.7%, who were considered a high-risk group (p < 0.01 vs. the groups with scores of 4–5 and >5, respectively). The IPA risk scores in the training set and the testing set were also analyzed by the ROC with an area under the ROC of 0.7152 and 0.6912. In this study, 57 patients received antifungal prophylaxis; the incidence of IPA was 1.8%, which was significantly lower after prophylactic antifungal therapy (p < 0.001). Conclusions: A weighted risk score for patients with liver failure, complicated with IPA, was established and confirmed in the testing cohort. Voriconazole prophylactic treatment to patients with liver failure with medium and high IPA risk can effectively prevent Aspergillus infection.